1997
DOI: 10.1093/toxsci/39.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sequentially Administered Stable Lead Isotopes to Investigate Changes in Blood Lead during Pregnancy in a Nonhuman Primate (Macaca fascicularis)

Abstract: The effects of pregnancy on the flux of lead from maternal bone were investigated in five females from a unique colony of cynomolgus monkeys (Macaca fascicularis) which had been dosed orally with lead (approximately 1100-1300 /ig Pb/kg body wt) throughout their lives (about 14 years). Through the use of stable lead isotopes ^Pb, ^Pb, and ^Pb, it was possible to differentiate between the lead contributed to blood lead from the skeleton and the lead contributed from the current oral dose. Blood samples and bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…For example, 7%-39% of lead in the fetal skeleton of macaque monkeys may be derived from the maternal skeleton. [27] Additional elemental sources in teeth include nonmilk liquids, solid foods, environmental dust, soil, and inhaled vapors. [23,28,29] When relating tooth chemistry to nursing behavior, nonmilk dietary inputs, and health, it is ideal to know: 1) how effectively specific elements are absorbed during digestion; 2) whether elements are selectively filtered out F I G U R E 1 Upper (maxillary) molar from a captive rhesus macaque (Macaca mulatta) shown from (A) front/mesial view and (B) top/occlusal view.…”
Section: Box 1 Hard Tissue Mineralization Is a Continuous Process Of Secretion And Maturationmentioning
confidence: 99%
“…For example, 7%-39% of lead in the fetal skeleton of macaque monkeys may be derived from the maternal skeleton. [27] Additional elemental sources in teeth include nonmilk liquids, solid foods, environmental dust, soil, and inhaled vapors. [23,28,29] When relating tooth chemistry to nursing behavior, nonmilk dietary inputs, and health, it is ideal to know: 1) how effectively specific elements are absorbed during digestion; 2) whether elements are selectively filtered out F I G U R E 1 Upper (maxillary) molar from a captive rhesus macaque (Macaca mulatta) shown from (A) front/mesial view and (B) top/occlusal view.…”
Section: Box 1 Hard Tissue Mineralization Is a Continuous Process Of Secretion And Maturationmentioning
confidence: 99%
“…The lead deposit in adult bone can act to replenish lead eliminated from blood by excretion, even long after exposure has ended 2226 . It can also act as a source of lead transfer to the fetus when maternal bone is resorbed for the production of the fetal skeleton 2730 .…”
Section: Basic Lead Biokineticsmentioning
confidence: 99%
“…Bone lead can contribute to elevated blood levels long after the exposure ceases (Fleming et al, 1997). Studies have reported that conditions such as ageing (Drasch, Bohm & Baur, 1987), osteoporosis (Gulson, Palmer & Bryce, 2002), pregnancy (Lagerkvist et al, 1996;Maldonado-Vega et al, 1996;Schuhmacher et al, 1996;Franklin et al, 1997;Gulson et al, 1997), lactation (Gulson et al, 2003(Gulson et al, , 2004, menopause and postmenopause (Hernandez-Avila et al, 2000;Gulson, Palmer & Bryce, 2002;Berkowitz et al, 2004;Nash et al, 2004;Popovic et al, 2005) increase bone resorption and consequently also increase lead levels in blood. Lead can be transferred from the mother to the fetus (Goyer, 1990;Graziano et al, 1990;Carbone et al, 1998) and also from the mother to infants via maternal milk (Gulson et al, 1998b;Ettinger et al, 2006).…”
Section: Absorption Distribution and Eliminationmentioning
confidence: 99%